Fatigue-resistant low-temperature-resistant elastic material and preparation method thereof
By using ultra-low crystallization rate neoprene and homemade Eucommia rubber in passenger car air spring elastic materials, combined with multiple components such as compound plasticizers, the specific feeding sequence solves the problem of insufficient fatigue resistance and low temperature resistance of elastic materials in the prior art in the preparation process, and achieves the effect of extending the service life of rubber airbags.
Patent Information
- Application Number
- CN202411957987.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-14
AI Technical Summary
The existing passenger car air spring elastic materials have shortcomings in fatigue resistance and low temperature resistance, resulting in a short service life of rubber airbags.
Ultra-low crystallization rate neoprene and homemade Eucommia ulmoide rubber are used to form a synergistic effect with multiple components such as compound plasticizers. During the preparation process, the fatigue resistance and low temperature resistance of the elastic material are improved.
At the same time, the fatigue resistance and low temperature resistance of elastic materials are improved, thereby extending the service life of rubber airbags.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of formula processing of polymer materials, and in particular to a fatigue-resistant and low-temperature-resistant elastic material and a preparation method thereof. Background Art
[0002] Passenger car air springs are key elastic components in passenger car air suspension systems. Air springs are composed of rubber airbags and metal sealing parts. The volume and pressure of the airbags are adjusted by inflation and deflation, thereby supporting the vehicle and adjusting the suspension height and hardness. The rubber airbag is composed of elastic materials and is a vulnerable component of the air spring. The most common failure of the rubber airbag is material aging caused by fatigue. Therefore, fatigue resistance is the biggest factor affecting the service life of the rubber airbag. Secondly, the weather resistance of the rubber airbag needs to be considered. China has a vast territory and a large climate difference between the north and the south. Therefore, weather resistance must be taken into consideration, especially low temperature resistance, because too low a temperature will directly cause damage to the rubber airbag.
[0003] Existing passenger car air spring elastic materials are mainly natural rubber system, chloroprene rubber system and a combination of the two rubbers. However, natural rubber has poor aging resistance and is not suitable for use as an elastic material for air springs. Although chloroprene rubber has excellent aging resistance, its mechanical properties are lower than those of natural rubber. Therefore, the use of the two rubbers can relatively give play to their respective advantages, but there are still problems with poor fatigue resistance and low temperature resistance.
[0004] CN101585938A discloses a formula for an air spring for automobiles, which is as follows by mass: a. Air spring inner and outer rubber formula: chloroprene rubber (50-100), natural rubber (50-100), magnesium oxide (0.5-5), stearic acid (0.5-3), antioxidant octylated diphenylamine (0.5-2.5); b. Air spring cord layer rubber formula: natural rubber (50-100), stearic acid (0.5-2), zinc oxide (2-5), antioxidant 2,2,4-trimethyl-1,2-dihydroquinoline polymer (0.5-3), antioxidant N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (0.5-2.5), tackifying resin A-90 (2-4). The inner and outer rubbers of the air spring prepared by the above formula have mechanical properties that meet the national standard technical requirements, but the inner and outer rubbers still do not have good low temperature resistance.
[0005] CN116355297A discloses a low-temperature resistant chloroprene rubber material, which is made of the following raw materials in parts by weight: 30-45 parts of chloroprene rubber, 10-20 parts of nitrile rubber, 35-50 parts of carbon black, 5-10 parts of plasticizer, 4-6 parts of epoxidized rapeseed oil, 1.5-3 parts of antioxidant, 1-3 parts of zinc oxide, 1-3 parts of magnesium oxide, and 0.3-1 part of accelerator. This formula is made by using chloroprene rubber and nitrile rubber that can effectively inhibit the low-temperature crystallization of chloroprene rubber. The material has good low-temperature resistance but poor fatigue resistance.
[0006] CN115785538A discloses a fatigue-resistant rubber and a preparation method thereof. The fatigue-resistant rubber comprises, by weight, 60-100 parts of natural rubber, 10-35 parts of trans-1,4-polyisoprene rubber, 20-40 parts of carbon black, 10-20 parts of white carbon black, 2-8 parts of carbon nanotubes, 2-5 parts of plasticizer, 1-3 parts of antioxidant, 1-4 parts of zinc oxide, 1-3 parts of stearic acid, 0.5-3 parts of sulfur and 0.5-2 parts of accelerator. Although this formula improves the fatigue resistance of the rubber, it fails to improve the low temperature resistance of the rubber.
[0007] It can be seen that how to simultaneously improve the fatigue resistance and low temperature resistance of elastic materials, thereby extending the service life of rubber airbags, is a technical problem that needs to be solved urgently. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a fatigue-resistant and low-temperature-resistant elastic material and a preparation method thereof. By using ultra-low crystallization rate chloroprene rubber and homemade eucommia rubber in combination, and combining multiple components such as compound plasticizers to form a synergistic effect, and adopting a specific adding sequence in the preparation process, the fatigue resistance and low-temperature resistance of the elastic material can be improved at the same time, thereby extending the service life of the rubber airbag.
[0009] The present invention provides a fatigue-resistant and low-temperature-resistant elastic material, wherein the elastic material comprises the following components: Ultra-low crystallization rate chloroprene rubber 80-95 parts; Eucommia rubber 5-20 parts; 3-5 parts of zinc oxide; 3-5 parts of magnesium oxide; 1-2 parts of stearic acid; Carbon black 10-30 parts; 5-25 parts of white carbon black; Compound plasticizer 10-25 parts; 5-15 parts of uniform resin; 1.5-3 parts of compound accelerator; 2-5 parts of antioxidant; Vulcanizing agent 0.5-1 part; Anti-scorch agent 0.5-2 parts.
[0010] Furthermore, the chloroprene rubber is one of the synthetic rubbers, and the main component is chloroprene.
[0011] Furthermore, the chloroprene rubber is a crystalline rubber, which slowly crystallizes and hardens at low temperatures, and its elasticity decreases rapidly, especially below 15°C.
[0012] Furthermore, the crystallization rate of the chloroprene rubber is affected by the molecular weight, molecular weight distribution and the regularity of the molecular chain. Adjusting the molecular weight distribution and the regularity of the molecular chain can effectively slow down the crystallization rate of the chloroprene rubber.
[0013] Furthermore, the chloroprene rubber is a mercaptan-regulated rubber, and the use of the mercaptan as a regulator can make the molecular weight distribution of the chloroprene rubber narrower and the molecular chain more regular.
[0014] Furthermore, the mercaptan-regulated rubber is the ultra-low crystallization rate chloroprene rubber, and the ultra-low crystallization rate chloroprene rubber has better low temperature resistance than conventional chloroprene rubber.
[0015] Furthermore, the ultra-low crystallization rate index is: below 0°C, the crystallization rate is above 144h, and the half-life is above 28h.
[0016] Furthermore, the Mooney viscosity value ML (1+4) of the ultra-low crystallization rate chloroprene rubber at 100° C. is 45-53.
[0017] Furthermore, the eucommia rubber is an isomer of natural rubber, and its main component is trans-polyisoprene.
[0018] Furthermore, the eucommia rubber has the dual properties of rubber and plastic. The use of the eucommia rubber in rubber products can significantly delay the generation of micro cracks and the expansion of local cracks, and the prepared products have good fatigue resistance.
[0019] Furthermore, the preparation method of the eucommia rubber is as follows: Step 1: Take eucommia seeds as raw materials, physically crush them by a crusher and a ball mill, remove impurities, and the content of eucommia rubber is 40-60% based on the total mass of the remaining raw materials in step 1; Step 2: Then, an ultra-fast water-based crushing process is used to continue to remove impurities in the eucommia rubber. After the impurities are removed, the content of the eucommia rubber is 70-80% based on the total mass of the remaining raw materials in step 2; Step 3: Finally, the eucommia rubber is extracted and purified by an organic solvent to remove impurities, and then the organic solvent is removed by a flash evaporation process. After drying, the content of the eucommia rubber is 95-99% based on the total mass of the remaining raw materials in step 3.
[0020] Furthermore, in step 1, the number of crushing and grinding is at least 1 time.
[0021] Furthermore, in step 1, the diameter of the zirconium beads of the ball mill is 0.3-1 cm, and the grinding time is 3-5 min.
[0022] Furthermore, in step 2, the ultra-fast water-based crushing process uses ultra-strong high-speed dispersion equipment to transmit shear force through the water phase to remove impurities in the eucommia rubber.
[0023] Furthermore, in step 2, the rotation speed of the ultra-strong high-speed dispersing equipment is 1500-2000 r / min, and the crushing time is 3-5 min.
[0024] Furthermore, in step 3, the organic solvent is one of chloroform, tetrahydrofuran, benzene or toluene.
[0025] Furthermore, in step 3, the flash evaporation process is to inject the solution containing the eucommia rubber into boiling water, and the eucommia rubber solid is obtained after the solvent evaporates rapidly.
[0026] Furthermore, the zinc oxide is an activator and a vulcanizing agent for the elastic material.
[0027] Furthermore, the average particle size of the zinc oxide is 50-70 nm, and the specific surface area is 30-50 m 2 / g.
[0028] Furthermore, the average particle size of the magnesium oxide is 80-100 nm, and the iodine adsorption value is 80-120 mg / g.
[0029] Furthermore, the stearic acid is a plasticizer and softener for the elastic material, and is used to improve the plasticity and softness of the elastic material; the stearic acid has a lubricating effect, and can reduce the friction resistance during the preparation process; the stearic acid is also beneficial to the dispersion of fillers such as the carbon black and the white carbon black, so that the filler is more evenly distributed in the elastic material.
[0030] Furthermore, the carbon black can form a large number of physical and chemical bonds with the molecules of the elastic material, filling the gaps in the elastic material, making the elastic material tighter, thereby improving the strength and hardness of the elastic material; the carbon black can also form a hard structure in the elastic material, which can effectively resist wear and extend the service life of the elastic material.
[0031] Furthermore, the carbon black is of the type N330, N550, N774 or a mixture of several of them.
[0032] Furthermore, the white carbon black can improve the strength, heat resistance, wear resistance and tear resistance of the elastic material.
[0033] Furthermore, the compound plasticizer reduces the glass transition temperature of the elastic material by physical means. On the one hand, the compound plasticizer increases the effective volume of the molecular chain of the elastic material. On the other hand, the compound plasticizer is inserted between the molecular chains of the elastic material, weakening the van der Waals force and other secondary bonds between the molecular chains of the elastic material, reducing the entanglement between the molecular chains, thereby improving the low temperature resistance and flexibility of the elastic material.
[0034] Furthermore, the ester group of the lipid plasticizer can add to the carbon-carbon double bond on the molecular chain of the elastic material to form a branched structure. This method of inhibiting crystallization by chemical reaction and physical method has an additive effect, which can effectively enhance the low temperature resistance of the elastic material.
[0035] Furthermore, the compound plasticizer includes a main plasticizer and a secondary plasticizer, and the ratio of the main plasticizer to the secondary plasticizer is (1-4):1.
[0036] Furthermore, the main plasticizer is one of dioctyl sebacate, dioctyl adipate or di[2-(2-butoxyethoxy)ethyl adipate].
[0037] Furthermore, the secondary plasticizer is one of ethyl oleate, butyl oleate, trioctyl phosphate or diisobutyl adipate.
[0038] Furthermore, the uniform resin is C5 petroleum resin, which is used to increase the compatibility and dispersibility of the ultra-low crystallization rate chloroprene rubber and the eucommia rubber, and the mixing effect is better.
[0039] Furthermore, the compound accelerator can shorten the vulcanization time.
[0040] Furthermore, the compound accelerator includes a main accelerator and a secondary accelerator, and the ratio of the main accelerator to the secondary accelerator is (1-4):1.
[0041] Furthermore, the primary accelerator is one of 1,2-ethylenethiourea, 3-methyl-2-thiazolethione or N,N,N′-trimethylthiourea.
[0042] Furthermore, the secondary accelerator is one of 2,2'-dibenzothiazyl disulfide, N-cyclohexyl-2-benzothiazole sulfenamide, tetramethylthiuram monosulfide or hexamethylenetetramine.
[0043] Furthermore, the antioxidant is used to delay the aging process of the elastic material.
[0044] Furthermore, the antioxidant is one or a mixture of 4-methyl-N-[4-(anilino)phenyl]benzenesulfonamide, N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine, 4,4'-dioctyldiphenylamine, 2-mercaptobenzimidazole, and N-isopropyl-N-phenylphenylenediamine.
[0045] Furthermore, the vulcanizing agent can cause a cross-linking reaction between the molecular chains of the elastic material, connecting the originally linear molecular chains of the elastic material into a three-dimensional network structure. This structural change significantly increases the elasticity and strength of the elastic material; in addition, the mechanical properties and stability of the elastic material after vulcanization treatment are improved.
[0046] Furthermore, the vulcanizing agent includes the zinc oxide and also includes sulfur and / or dicumyl peroxide.
[0047] Furthermore, the scorch retarder is used to prevent premature vulcanization, also known as scorch, of the elastomeric material during processing.
[0048] Furthermore, the anti-scorch agent is one or a mixture of N-cyclohexylthiophthalamide, N,N-m-phenylene bismaleimide, and N,N-tetramethyl dithiodithioamide.
[0049] The present invention provides a method for preparing a fatigue-resistant and low-temperature-resistant elastic material, the method comprising the following steps: Step 1: Softening: drying the ultra-low crystallization rate chloroprene rubber and the eucommia rubber in an oven; Step 2: mastication: firstly put the ultra-low crystallization rate chloroprene rubber into the internal mixer for mastication, and then put the eucommia rubber into the internal mixer for mastication; Step 3: one-stage mixing: the zinc oxide, the magnesium oxide, the stearic acid, the uniform resin, the antioxidant and the anti-scorch agent are continuously added to the internal mixer for the one-stage mixing, during which the mixing is performed once, and then the carbon black, the white carbon black and the compound plasticizer are added to continue the one-stage mixing, during which the mixing is performed once more, and when the temperature of the mixed rubber reaches 120-125° C., the rubber is discharged and cooled to obtain a one-stage mixed rubber; Step 4: two-stage mixing: take the first-stage mixed rubber and tightly coat it on the roller surface of the open mixer, then add the compound accelerator and the vulcanizer, pass the roller, three knives on the left and right, make a triangular package, adjust the roller distance to produce a sheet, cool it, and obtain the elastic material.
[0050] Furthermore, in step 1, the drying temperature of the oven is 50-70° C., and the drying time is 10-30 min.
[0051] Furthermore, in step 2, the temperature of the internal mixer is 50-60° C., and the rotation speed is 30-40 r / min.
[0052] Furthermore, in step 2, the plasticizing time of the ultra-low crystallization rate chloroprene rubber is 1-2 minutes, and the plasticizing time of the eucommia rubber is 0.5-1 minute.
[0053] Furthermore, in the step 3, the mixing time after adding the zinc oxide, the magnesium oxide, the stearic acid, the uniform resin, the antioxidant and the anti-scorch agent is 1-3 minutes, and the mixing time after adding the carbon black, the white carbon black and the compound plasticizer is 2-4 minutes.
[0054] Furthermore, in step 4, the roller temperature of the open mixing mill is 45-55° C., and the roller distance in the two-stage mixing process is 2-3 mm.
[0055] Furthermore, in step 4, the number of times of passing the rollers is 4-6 times, the number of times of making triangle packages is 5-7 times, and the roller distance of the sheet is 5-6 mm.
[0056] An air spring for a passenger vehicle, comprising the elastic material.
[0057] Beneficial Effects of the Invention 1. The present invention unexpectedly selects chloroprene rubber and eucommia rubber for use, wherein the chloroprene rubber is a mercaptan-regulated rubber. Using mercaptan as a regulator can make the molecular weight distribution of the chloroprene rubber narrower and the molecular chain more regular, and can effectively slow down the crystallization rate of the chloroprene rubber, that is, obtain ultra-low crystallization rate chloroprene rubber [Mooney viscosity value ML (1+4) 100°C is 45-53], which has better low temperature resistance than conventional chloroprene rubber; in addition, the eucommia rubber of the present invention is obtained by a homemade method, that is, by combining the three-step extraction method of physical crushing, ultra-speed water-based crushing process and extraction purification, and combining specific extraction parameters, so as to prepare eucommia rubber with a specific structure, and its unique microcrystalline network structure can simultaneously inhibit the generation and propagation of cracks inside the rubber, and can effectively improve the fatigue resistance of the elastic material. Therefore, the present invention unexpectedly uses ultra-low crystallization rate chloroprene rubber and homemade eucommia rubber for use, and combines multiple components such as compound plasticizers to form a synergistic effect, which can simultaneously improve the fatigue resistance and low temperature resistance of the elastic material.
[0058] 2. The present invention unexpectedly uses a primary plasticizer and a secondary plasticizer in combination. If only one plasticizer is used, for example, Dioctyl sebacate, although the elastic material can withstand low temperatures of about (-35)°C at this time, dioctyl sebacate has poor compatibility with the colloid and is easy to migrate to the surface of the colloid. The compound plasticizer of the present invention not only has good compatibility with the colloid, but also the prepared elastic material has better low temperature resistance.
[0059] 3. In the preparation process of the elastic material, the present invention adopts a specific order of adding materials. First, zinc oxide, magnesium oxide, stearic acid, uniform resin, antioxidant and anti-scorch agent are added to the system of ultra-low crystallization rate chloroprene rubber and eucommia rubber for one-stage mixing, and then carbon black, white carbon black and compound plasticizer are added for one-stage mixing, and finally compound accelerator and vulcanizing agent are added for two-stage mixing. Zinc oxide reacts with stearic acid to form zinc stearate, which has lubrication and vulcanization promoting effects, helps to improve the fluidity and vulcanization efficiency of the colloid, and the addition of antioxidant and anti-scorch agent can prevent scorch from occurring during the preparation process. By adding these basic materials first, the stability of the mixing process can be ensured, providing favorable conditions for the subsequent addition of other materials. Carbon black and white carbon black, as reinforcing agents of colloids, can significantly improve the tensile strength, tear strength and wear resistance of colloids. At this time, the colloid has been mixed to a certain extent, and the temperature, pressure and dispersibility have reached a more suitable state, which is conducive to the full dispersion of carbon black and white carbon black in the colloid. The addition of compound plasticizers can reduce the viscosity of the colloid, making the colloid easier to mix and shape in the subsequent preparation process, and can further improve the low temperature resistance of the elastic material. Compound accelerators can accelerate the vulcanization reaction of colloids, and vulcanizers are the key substances of vulcanization reactions. The final addition can ensure the smooth progress of the vulcanization reaction, while avoiding premature contact with other materials to cause adverse reactions. DETAILED DESCRIPTION
[0060] Example 1 Preparation method of fatigue-resistant and low-temperature-resistant elastic material: Step 1: Softening: 95 parts by weight of ultra-low crystallization rate chloroprene rubber and 5 parts by weight of eucommia rubber are dried in an oven at a temperature of 50°C for 10 minutes. The Mooney viscosity value ML (1+4) of the ultra-low crystallization rate chloroprene rubber at 100°C is 45. The preparation method of eucommia rubber is as follows: ① Take eucommia seeds as raw materials, and physically crush them by a crusher and a ball mill. The diameter of the zirconium beads of the ball mill is 0.3 cm, and the grinding time is 3 minutes. After removing impurities, the total mass of the remaining raw materials in step ① is used as percentage. ② Then, an ultra-high speed water-based crushing process is used to further remove impurities in the eucommia rubber. The speed of the ultra-high speed dispersing equipment is 1500r / min, and the crushing time is 3min. After removing impurities, the content of eucommia rubber is 70% based on the total mass of the remaining raw materials in step ② as a percentage basis; ③ Finally, chloroform is used to extract and purify the eucommia rubber. After removing impurities, the organic solvent is removed by a flash evaporation process. After drying, the content of eucommia rubber is 95% based on the total mass of the remaining raw materials in step ③ as a percentage basis.
[0061] Step 2: Plastication: First, ultra-low crystallization rate chloroprene rubber is put into the internal mixer for plastication for 1 minute, and then eucommia rubber is put into the internal mixer for plastication for 0.5 minute. The temperature of the internal mixer is 50°C and the speed is 30r / min.
[0062] Step 3: Mixing: 3 parts by weight of zinc oxide, 3 parts by weight of magnesium oxide, 1 part by weight of stearic acid, 5 parts by weight of C5 petroleum resin, 2 parts by weight of N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine and 0.5 parts by weight of N-cyclohexylthiophthalamide were added to the internal mixer and mixed for 1 minute. The average particle size of zinc oxide was 50 nm and the specific surface area was 30 m 2 / g, the average particle size of magnesium oxide is 80nm, and the iodine adsorption value is 80mg / g. During this process, it is extracted once, and then 10 parts by weight of carbon black, 5 parts by weight of white carbon black and 10 parts by weight of compound plasticizer are added to continue mixing for 2 minutes. Among them, the model of carbon black is N550, the main plasticizer is 5 parts by weight of dioctyl sebacate, and the secondary plasticizer is 5 parts by weight of ethyl oleate. During this process, it is extracted once again. When the temperature of the mixed rubber reaches 120°C, it is discharged and cooled to obtain a mixed rubber.
[0063] Step 4: Two-stage mixing: Take a section of the mixed rubber and tightly wrap it on the roller surface of the open mill. The roller temperature of the open mill is 45°C and the roller distance is 2mm. Then add 1.5 parts by weight of the compound accelerator and 0.5 parts by weight of the vulcanizer, wherein the main accelerator is 0.75 parts by weight of 1,2-ethylenethiourea, the secondary accelerator is 0.75 parts by weight of 2,2'-dibenzothiazole disulfide, and the vulcanizer is a mixture of 0.3 parts by weight of zinc oxide and 0.2 parts by weight of sulfur. Roll over 4 times, three knives on each side, make triangle packages 5 times, adjust the roller distance to 5mm to discharge the sheet, cool it, and obtain the elastic material, which is then tested for performance.
[0064] Example 2 Preparation method of fatigue-resistant and low-temperature-resistant elastic material: Step 1: Softening: 85 parts by weight of ultra-low crystallization rate chloroprene rubber and 15 parts by weight of eucommia rubber are dried in an oven at a temperature of 60°C for 20 minutes. The Mooney viscosity value ML (1+4) of the ultra-low crystallization rate chloroprene rubber at 100°C is 53. The preparation method of eucommia rubber is as follows: ① Take eucommia seeds as raw materials, and physically crush them through 2 crushers and 1 ball mill. The diameter of the zirconium beads of the ball mill is 0.5 cm, and the grinding time is 4 minutes. After removing impurities, the total mass of the remaining raw materials in step ① is used as a percentage. ② Then, an ultra-high speed water-based crushing process is used to further remove impurities in the eucommia rubber, the speed of the ultra-strong high-speed dispersing equipment is 1800r / min, the crushing time is 4min, after removing impurities, the content of eucommia rubber is 75% based on the total mass of the remaining raw materials in step ② as a percentage basis; ③ Finally, tetrahydrofuran is used to extract and purify the eucommia rubber, after removing impurities, the organic solvent is removed by a flash evaporation process, and after drying, the content of eucommia rubber is 98% based on the total mass of the remaining raw materials in step ③ as a percentage basis.
[0065] Step 2: Plastication: First, ultra-low crystallization rate chloroprene rubber is put into the internal mixer for plastication for 1 minute, and then eucommia rubber is put into the internal mixer for plastication for 0.5 minute. The temperature of the internal mixer is 55°C and the speed is 35r / min.
[0066] Step 3: Mixing: 4 parts by weight of zinc oxide, 4 parts by weight of magnesium oxide, 1.5 parts by weight of stearic acid, 10 parts by weight of C5 petroleum resin, 4 parts by weight of 4-methyl-N-[4-(anilino)phenyl]benzenesulfonamide and 1 part by weight of N,N-phenylene bismaleimide were added to the internal mixer and mixed for 2 minutes. The average particle size of zinc oxide was 70 nm and the specific surface area was 50 m 2 / g, the average particle size of magnesium oxide is 100nm, and the iodine adsorption value is 120mg / g. During this process, it is extracted once, and then 20 parts by weight of carbon black, 15 parts by weight of white carbon black and 20 parts by weight of compound plasticizer are added to continue mixing for 3 minutes. Among them, the model of carbon black is N774, the main plasticizer is 15 parts by weight of dioctyl adipate, and the secondary plasticizer is 5 parts by weight of trioctyl phosphate. During this process, it is extracted once again. When the temperature of the mixed rubber reaches 120°C, it is discharged and cooled to obtain a mixed rubber.
[0067] Step 4: two-stage mixing: take a section of mixed rubber and tightly coat it on the roller surface of the open mill. The roller temperature of the open mill is 50°C and the roller distance is 2mm. Then add 2 parts by weight of compound accelerator and 0.8 parts by weight of vulcanizer, wherein the main accelerator is 1.5 parts by weight of 3-methyl-2-thiazolethione, the secondary accelerator is 0.5 parts by weight of N-cyclohexyl-2-benzothiazolesulfonamide, and the vulcanizer is a mixture of 0.4 parts by weight of zinc oxide and 0.4 parts by weight of diisopropylbenzene peroxide. Roll over 5 times, three knives on each side, make triangle packages 6 times, adjust the roller distance to 5mm to discharge the sheet, cool it, and obtain the elastic material, which is then tested for performance.
[0068] Example 3 Preparation method of fatigue-resistant and low-temperature-resistant elastic material: Step 1: Softening: Take 80 parts by weight of ultra-low crystallization rate chloroprene rubber and 20 parts by weight of eucommia rubber and dry them in an oven. The temperature of the oven is 70°C and the drying time is 30 minutes. The Mooney viscosity value ML (1+4) of the ultra-low crystallization rate chloroprene rubber at 100°C is 50. The preparation method of eucommia rubber is as follows: ① Take eucommia seeds as raw materials, and physically crush them through 3 crushers and 2 ball mills. The diameter of the zirconium beads of the ball mill is 1 cm, and the grinding time is 5 minutes. After removing impurities, the total mass of the remaining raw materials in step ① is used as a percentage ② Then, an ultra-high speed water-based crushing process is used to further remove impurities in the eucommia rubber, the speed of the ultra-strong high-speed dispersing equipment is 2000r / min, the crushing time is 5min, after removing impurities, the content of eucommia rubber is 80% based on the total mass of the remaining raw materials in step ② as a percentage basis; ③ Finally, toluene is used to extract and purify the eucommia rubber, after removing impurities, the organic solvent is removed by a flash evaporation process, and after drying, the content of eucommia rubber is 99% based on the total mass of the remaining raw materials in step ③ as a percentage basis.
[0069] Step 2: Plastication: First, ultra-low crystallization rate chloroprene rubber is put into the internal mixer for plastication for 2 minutes, and then eucommia rubber is put into the internal mixer for plastication for 1 minute. The temperature of the internal mixer is 60°C and the speed is 40r / min.
[0070] Step 3: Mixing: Add 5 parts by weight of zinc oxide, 5 parts by weight of magnesium oxide, 2 parts by weight of stearic acid, 15 parts by weight of C5 petroleum resin, 5 parts by weight of 2-mercaptobenzimidazole and 2 parts by weight of N,N-tetramethyl dithiodithiocarboxamide into the internal mixer and mix for 3 minutes. The average particle size of zinc oxide is 65 nm and the specific surface area is 42 m 2 / g, the average particle size of magnesium oxide is 88nm, and the iodine adsorption value is 105mg / g. During this process, it is extracted once, and then 30 parts by weight of carbon black, 25 parts by weight of white carbon black and 25 parts by weight of compound plasticizer are added to continue mixing for 4 minutes. Among them, the model of carbon black is N330, the main plasticizer is 20 parts by weight of di[2-(2-butoxyethoxy)ethyl adipate], and the secondary plasticizer is 5 parts by weight of diisobutyl adipate. During this process, it is extracted once again. When the temperature of the mixed rubber reaches 125°C, it is discharged and cooled to obtain a mixed rubber.
[0071] Step 4: two-stage mixing: take a section of mixed rubber and tightly coat it on the roller surface of the open mill. The roller temperature of the open mill is 55°C and the roller distance is 3mm. Then add 3 parts by weight of compound accelerator and 1 part by weight of vulcanizing agent, wherein the main accelerator is 2.4 parts by weight of N,N,N′-trimethylthiourea, the secondary accelerator is 0.6 parts by weight of hexamethylenetetramine, and the vulcanizing agent is a mixture of 0.4 parts by weight of zinc oxide, 0.3 parts by weight of sulfur and 0.3 parts by weight of diisopropylbenzene peroxide. Roll over 6 times, three knives on each side, make triangle packages 7 times, adjust the roller distance to 6mm to discharge the sheet, cool it, and obtain the elastic material, which is then tested for performance.
[0072] Comparative Example 1 Preparation method of elastic material: Step 1: Softening: 95 parts by weight of ultra-low crystallization rate chloroprene rubber and 5 parts by weight of commercially available eucommia rubber are dried in an oven at a temperature of 50°C for 10 minutes. The Mooney viscosity value ML (1+4) of the ultra-low crystallization rate chloroprene rubber at 100°C is 45. Step 2: Plastication: First, ultra-low crystallization rate chloroprene rubber is put into the internal mixer for plastication for 1 minute, and then eucommia rubber is put into the internal mixer for plastication for 0.5 minute. The temperature of the internal mixer is 50°C and the speed is 30r / min.
[0073] Step 3: Mixing: 3 parts by weight of zinc oxide, 3 parts by weight of magnesium oxide, 1 part by weight of stearic acid, 5 parts by weight of C5 petroleum resin, 2 parts by weight of N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine and 0.5 parts by weight of N-cyclohexylthiophthalamide were added to the internal mixer and mixed for 1 minute. The average particle size of zinc oxide was 50 nm and the specific surface area was 30 m 2 / g, the average particle size of magnesium oxide is 80nm, and the iodine adsorption value is 80mg / g. During this process, it is extracted once, and then 10 parts by weight of carbon black, 5 parts by weight of white carbon black and 10 parts by weight of compound plasticizer are added to continue mixing for 2 minutes. Among them, the model of carbon black is N550, the main plasticizer is 5 parts by weight of dioctyl sebacate, and the secondary plasticizer is 5 parts by weight of ethyl oleate. During this process, it is extracted once again. When the temperature of the mixed rubber reaches 120°C, it is discharged and cooled to obtain a mixed rubber.
[0074] Step 4: Two-stage mixing: Take a section of the mixed rubber and tightly wrap it on the roller surface of the open mill. The roller temperature of the open mill is 45°C and the roller distance is 2mm. Then add 1.5 parts by weight of the compound accelerator and 0.5 parts by weight of the vulcanizer, wherein the main accelerator is 0.75 parts by weight of 1,2-ethylenethiourea, the secondary accelerator is 0.75 parts by weight of 2,2'-dibenzothiazole disulfide, and the vulcanizer is a mixture of 0.3 parts by weight of zinc oxide and 0.2 parts by weight of sulfur. Roll over 4 times, three knives on each side, make triangle packages 5 times, adjust the roller distance to 5mm to discharge the sheet, cool it, and obtain the elastic material, which is then tested for performance.
[0075] Comparative Example 2 Preparation method of elastic material: Step 1: Softening: 95 parts by weight of ultra-low crystallization rate chloroprene rubber and 5 parts by weight of eucommia rubber are dried in an oven at a temperature of 50°C for 10 minutes. The Mooney viscosity value ML (1+4) of the ultra-low crystallization rate chloroprene rubber at 100°C is 45. The preparation method of eucommia rubber is as follows: ① Take eucommia seeds as raw materials, and physically crush them by a crusher and a ball mill. The diameter of the zirconium beads of the ball mill is 0.3 cm, and the grinding time is 3 minutes. After removing impurities, the total mass of the remaining raw materials in step ① is used as percentage. ② Then, an ultra-high speed water-based crushing process is used to further remove impurities in the eucommia rubber. The speed of the ultra-high speed dispersing equipment is 1500r / min, and the crushing time is 3min. After removing impurities, the content of eucommia rubber is 70% based on the total mass of the remaining raw materials in step ② as a percentage basis; ③ Finally, chloroform is used to extract and purify the eucommia rubber. After removing impurities, the organic solvent is removed by a flash evaporation process. After drying, the content of eucommia rubber is 95% based on the total mass of the remaining raw materials in step ③ as a percentage basis.
[0076] Step 2: Plastication: First, ultra-low crystallization rate chloroprene rubber is put into the internal mixer for plastication for 1 minute, and then eucommia rubber is put into the internal mixer for plastication for 0.5 minute. The temperature of the internal mixer is 50°C and the speed is 30r / min.
[0077] Step 3: Mixing: 3 parts by weight of zinc oxide, 3 parts by weight of magnesium oxide, 1 part by weight of stearic acid, 5 parts by weight of C5 petroleum resin, 2 parts by weight of N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine and 0.5 parts by weight of N-cyclohexylthiophthalamide were added to the internal mixer and mixed for 1 minute. The average particle size of zinc oxide was 50 nm and the specific surface area was 30 m 2 / g, the average particle size of magnesium oxide is 80nm, and the iodine adsorption value is 80mg / g. During this process, it is extracted once, and then 10 parts by weight of carbon black, 5 parts by weight of white carbon black and 10 parts by weight of dioctyl sebacate are added to continue mixing for 2 minutes. Among them, the model of carbon black is N550. During this process, it is extracted once again. When the temperature of the mixed rubber reaches 120℃, it is discharged and cooled to obtain a mixed rubber.
[0078] Step 4: Two-stage mixing: Take a section of the mixed rubber and tightly wrap it on the roller surface of the open mill. The roller temperature of the open mill is 45°C and the roller distance is 2mm. Then add 1.5 parts by weight of the compound accelerator and 0.5 parts by weight of the vulcanizer, wherein the main accelerator is 0.75 parts by weight of 1,2-ethylenethiourea, the secondary accelerator is 0.75 parts by weight of 2,2'-dibenzothiazole disulfide, and the vulcanizer is a mixture of 0.3 parts by weight of zinc oxide and 0.2 parts by weight of sulfur. Roll over 4 times, three knives on each side, make triangle packages 5 times, adjust the roller distance to 5mm to discharge the sheet, cool it, and obtain the elastic material, which is then tested for performance.
[0079] Comparative Example 3 Preparation method of elastic material: Step 1: Softening: 95 parts by weight of ultra-low crystallization rate chloroprene rubber and 5 parts by weight of eucommia rubber are dried in an oven at a temperature of 50°C for 10 minutes. The Mooney viscosity value ML (1+4) of the ultra-low crystallization rate chloroprene rubber at 100°C is 45. The preparation method of eucommia rubber is as follows: ① Take eucommia seeds as raw materials, and physically crush them by a crusher and a ball mill. The diameter of the zirconium beads of the ball mill is 0.3 cm, and the grinding time is 3 minutes. After removing impurities, the total mass of the remaining raw materials in step ① is used as percentage. ② Then, an ultra-high speed water-based crushing process is used to further remove impurities in the eucommia rubber. The speed of the ultra-high speed dispersing equipment is 1500r / min, and the crushing time is 3min. After removing impurities, the content of eucommia rubber is 70% based on the total mass of the remaining raw materials in step ② as a percentage basis; ③ Finally, chloroform is used to extract and purify the eucommia rubber. After removing impurities, the organic solvent is removed by a flash evaporation process. After drying, the content of eucommia rubber is 95% based on the total mass of the remaining raw materials in step ③ as a percentage basis.
[0080] Step 2: Plastication: First, ultra-low crystallization rate chloroprene rubber is put into the internal mixer for plastication for 1 minute, and then eucommia rubber is put into the internal mixer for plastication for 0.5 minute. The temperature of the internal mixer is 50°C and the speed is 30r / min.
[0081] Step 3: One-stage mixing: 3 parts by weight of zinc oxide, 3 parts by weight of magnesium oxide, 1 part by weight of stearic acid, 5 parts by weight of C5 petroleum resin, 2 parts by weight of N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine, 0.5 parts by weight of N-cyclohexylthiophthalamide, 10 parts by weight of carbon black, 5 parts by weight of white carbon black, 10 parts by weight of compound plasticizer, 1.5 parts by weight of compound accelerator and 0.5 parts by weight of vulcanizing agent were added to the internal mixer and mixed for 3 minutes. The average particle size of zinc oxide was 50 nm and the specific surface area was 30 m 2 / g, the average particle size of magnesium oxide is 80nm, the iodine adsorption value is 80mg / g, the model of carbon black is N550, the main plasticizer is 5 parts by weight of dioctyl sebacate, the secondary plasticizer is 5 parts by weight of ethyl oleate, the main accelerator is 0.75 parts by weight of 1,2-ethylenethiourea, the secondary accelerator is 0.75 parts by weight of 2,2'-dibenzothiazole disulfide, and the vulcanizing agent is a mixture of 0.3 parts by weight of zinc oxide and 0.2 parts by weight of sulfur. During this process, it is extracted once, and when the temperature of the mixed rubber reaches 120°C, it is discharged and cooled to obtain a mixed rubber.
[0082] Step 4: Two-stage mixing: Take a section of the mixed rubber and wrap it tightly on the roller surface of the open mixing mill. The roller temperature of the open mixing mill is 45°C, the roller distance is 2mm, the roller passes 4 times, three knives on each side, and triangle packs 5 times. Adjust the roller distance to 5mm to produce a sheet. Cool it to obtain the elastic material, and then conduct performance tests.
[0083] The fatigue resistance and low temperature resistance of the elastic materials in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1: Table 1 Comparison of fatigue resistance and low temperature resistance of elastic materials in Examples 1-3 and Comparative Examples 1-3
[0084] In summary, in the prior art (Comparative Examples 1-3), the fatigue resistance and low temperature resistance of the elastic material are not good enough. Comparative Example 1 does not use the homemade eucommia rubber of the present invention, but selects commercially available eucommia rubber, and the fatigue resistance of the elastic material prepared thereby is obviously poor; Comparative Example 2 does not use a compound plasticizer, but only uses dioctyl sebacate as a plasticizer, and the low temperature resistance of the elastic material prepared thereby is not good enough; Comparative Example 3 does not adopt a specific feeding sequence, but only mixes the materials at one time, and the fatigue resistance and low temperature resistance of the elastic material prepared thereby are obviously poor. Therefore, Examples 1-3 of the present invention use ultra-low crystallization rate chloroprene rubber and homemade eucommia rubber in combination, and combine multiple components such as compound plasticizers to form a synergistic effect, and adopt a specific feeding sequence in the preparation process, which can simultaneously improve the fatigue resistance and low temperature resistance of the elastic material, thereby extending the service life of the rubber airbag, that is, the present invention produces unexpected technical effects.
[0085] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.
Claims
1. A fatigue-resistant and low-temperature-resistant elastic material, characterized in that: The elastic material comprises the following components: Ultra-low crystallization rate chloroprene rubber 80-95 parts; Eucommia rubber 5-20 parts; 3-5 parts of zinc oxide; 3-5 parts of magnesium oxide; 1-2 parts of stearic acid; Carbon black 10-30 parts; 5-25 parts of white carbon black; Compound plasticizer 10-25 parts; 5-15 parts of uniform resin; 1.5-3 parts of compound accelerator; 2-5 parts of antioxidant; Vulcanizing agent 0.5-1 part; Anti-scorch agent 0.5-2 parts.
2. The elastic material according to claim 1, characterized in that The Mooney viscosity value ML (1+4) of the ultra-low crystallization rate chloroprene rubber at 100° C. is 45-53.
3. The elastic material according to claim 1, characterized in that The preparation method of the eucommia rubber is as follows: Step 1: Take eucommia seeds as raw materials, physically crush them by a crusher and a ball mill, remove impurities, and the content of eucommia rubber is 40-60% based on the total mass of the remaining raw materials in step 1; Step 2: Then, an ultra-fast water-based crushing process is used to continue to remove impurities in the eucommia rubber. After the impurities are removed, the content of the eucommia rubber is 70-80% based on the total mass of the remaining raw materials in step 2; Step 3: Finally, the eucommia rubber is extracted and purified by an organic solvent to remove impurities, and then the organic solvent is removed by a flash evaporation process. After drying, the content of the eucommia rubber is 95-99% based on the total mass of the remaining raw materials in step 3.
4. The elastic material according to claim 1, characterized in that The compound plasticizer comprises a main plasticizer and a secondary plasticizer, wherein the ratio of the main plasticizer to the secondary plasticizer is (1-4):1, the main plasticizer is one of dioctyl sebacate, dioctyl adipate or di[2-(2-butoxyethoxy)ethyl adipate], and the secondary plasticizer is one of ethyl oleate, butyl oleate, trioctyl phosphate or diisobutyl adipate.
5. The elastic material according to claim 1, characterized in that The compound accelerator comprises a main accelerator and a secondary accelerator, wherein the ratio of the main accelerator to the secondary accelerator is (1-4):1, the main accelerator is one of 1,2-ethylenethiourea, 3-methyl-2-thiazolethione or N,N,N′-trimethylthiourea, and the secondary accelerator is one of 2,2′-dibenzothiazole disulfide, N-cyclohexyl-2-benzothiazole sulfonamide, tetramethylthiuram monosulfide or hexamethylenetetramine.
6. The elastic material according to claim 1, characterized in that The antioxidant is one or a mixture of 4-methyl-N-[4-(anilino)phenyl]benzenesulfonamide, N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine, 4,4'-dioctyldiphenylamine, 2-mercaptobenzimidazole, and N-isopropyl-N-phenylphenylenediamine.
7. The elastic material according to claim 1, characterized in that The vulcanizing agent includes the zinc oxide and further includes sulfur and / or dicumyl peroxide.
8. The elastic material according to claim 1, characterized in that The anti-scorch agent is one or a mixture of N-cyclohexylthiophthalamide, N,N-m-phenylene bismaleimide, and N,N-tetramethyl dithiodithioamide.
9. A method for preparing the elastic material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: Step 1: Softening: drying the ultra-low crystallization rate chloroprene rubber and the eucommia rubber in an oven; Step 2: mastication: firstly put the ultra-low crystallization rate chloroprene rubber into the internal mixer for mastication, and then put the eucommia rubber into the internal mixer for mastication; Step 3: one-stage mixing: the zinc oxide, the magnesium oxide, the stearic acid, the uniform resin, the antioxidant and the anti-scorch agent are continuously added to the internal mixer for the one-stage mixing, during which the mixing is performed once, and then the carbon black, the white carbon black and the compound plasticizer are added to continue the one-stage mixing, during which the mixing is performed once more, and when the temperature of the mixed rubber reaches 120-125° C., the rubber is discharged and cooled to obtain a one-stage mixed rubber; Step 4: two-stage mixing: take the first-stage mixed rubber and tightly coat it on the roller surface of the open mixer, then add the compound accelerator and the vulcanizer, pass the roller, three knives on the left and right, make a triangular package, adjust the roller distance to produce a sheet, cool it, and obtain the elastic material.
10. A passenger car air spring, characterized in that: The air spring comprises the elastic material according to any one of claims 1-8.
Citation Information
Patent Citations
Air spring formulation for automobile
CN101585938A